(untitled) (Research, Society and Development, 2020)
Sapajus libidinosus is a species of primates, popularly known as capuchin monkey. The oral cavity of the monkeys may have pathogenic microbiota for human. Therefore, the study of the microbiota of these species is of great interest in unique health. The objective of the present article was to carry out a survey of the oral microbiota of Sapajus libidinosus, kept in captivity, in the Zoobotanical Park of Teresina (PI, Brazil). Ten chemically immobilized primates were used. Samples were collected from the oral mucosa along the maxillary muco-gingival transition, and these samples were sent to culture and microbiological identification. Most of the microorganisms found were Gram negative and E.coli was the most frequent, followed by Enterobacter spp, Klebsiella spp, Proteus mirabilis, Citrobacter spp.,Morganella morganii, as well as Gram positive bacteria of the type Staphylococcus spp. The data obtained demonstrated the presence of bacterial strains with potential risk of transmission to other animals kept in the park as well as humans in contact with these animals.